Three-Component One-Pot Synthesis of 4,6-Diarylpyrimidin-2(1H)-ones Catalyzed by 1-Methyl-3-[2-(sulfooxy)ethyl]-1H-imidazol-3-ium Chloride - Wan, Yu; Chen, Liang-Feng; Wang, Hai-Ying; Zhao, Ling-Ling; Huang, Shu-Ying; Liu, Gui-Xiang; Yue, Shu-Ning; Zhang, Wen-Li; Wu, Hui (Asian Journal of Chemistry, 2013)
An efficient, one-pot, three-component cyclocondensation reaction of aromatic aldehydes, aromatic ketone and urea catalyzed by 1-methyl-3-[2-(sulfooxy)ethyl]-1H-imidazol-3-ium chloride is developed to give 4,6-diarylpyrimidin-2(1H)-ones.